Brucella Orshitis That Imitate Testıcular Tumor: Case Report - Ayşe SAĞMAK TARTAR; Affan DENK (Namık Kemal Tıp Dergisi, 2016)

(untitled)
Brucellosis a disease that can occur with different clinical manifestations affecting all systems, causes difficulties in diagnosis and treatment. The genitourinary tract involvement in brucellosis is found in the ratio of 2-20%, and most often present with epididymoorchitis clinic. Sometimes it can mimic tumor by doing mass in the testicle. In this article; 21 year old patient who applied with pain and swelling in the testicles,diagnosed with testicular tumor according to clinical and radiological findings, and therefore done orchiectomy, then diagnosed Brucella orchitis according to the histopathological and serological evidence is presented. In particular, in endemic areas such as our country, in such cases with testicular mass, brucellosis should be considered in the differential diagnosis of non-specific granulomatous orchitis.